2020
DOI: 10.2463/mrms.mp.2018-0158
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Contrast-enhanced Area-detector CT vs Dynamic Contrast-enhanced Perfusion MRI vs FDG-PET/CT: Comparison of Utility for Quantitative Therapeutic Outcome Prediction for NSCLC Patients Undergoing Chemoradiotherapy

Abstract: Purpose: To directly compare the utility for therapeutic outcome prediction of dynamic first-pass contrast-enhanced (CE)-perfusion area-detector computed tomography (ADCT), MR imaging assessed with the same mathematical method and 2-[fluorine-18]-fluoro-2-deoxy-d-glucose-positron emission tomography combined with CT (PET/CT) for non-small cell lung cancer (NSCLC) patients treated with chemoradiotherapy. Materials and Methods:Forty-three consecutive stage IIIB NSCLC patients, consisting of 25 males (mean age ± … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 31 publications
1
12
0
Order By: Relevance
“…Intra‐ and inter‐observer agreements for MTR asym at 3.5 ppm, ADC, and SUV max measurements were less than 10% and close to those previously reported 9,12,20 …”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Intra‐ and inter‐observer agreements for MTR asym at 3.5 ppm, ADC, and SUV max measurements were less than 10% and close to those previously reported 9,12,20 …”
Section: Discussionsupporting
confidence: 85%
“…Different imaging techniques have been used for the evaluation or prediction of the therapeutic effect of CRT for NSCLC patients, such as chest radiography, computed tomography (CT), positron emission tomography (PET) or PET fused with CT (PET/CT) by means of 2‐[fluorine‐18]‐fluoro‐2‐deoxy‐D‐glucose (FDG), and magnetic resonance imaging (MRI). In particular, contrast‐enhanced (CE) MRI, dynamic CE‐MRI, and diffusion‐weighted imaging (DWI) sequences have been commonly used according to clinical or academic practices 2–12 …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The model used features extracted from lesions, margins, and blood vessels and reached an area under the curve (AUC) of 0.73 in a test cohort with 176 patients. Seki et al had demonstrated the usefulness of CT and Positron Emission Tomography (PET)/CT in the early prediction of chemoradiotherapy in NSCLC (24). In the present study, we constructed a radiomic model that used pre-chemotherapy CT images to predict the NSCLC chemotherapy response.…”
Section: Introductionmentioning
confidence: 96%
“…Seki et al. had demonstrated the usefulness of CT and Positron Emission Tomography (PET)/CT in the early prediction of chemoradiotherapy in NSCLC ( 24 ). In the present study, we constructed a radiomic model that used pre-chemotherapy CT images to predict the NSCLC chemotherapy response.…”
Section: Introductionmentioning
confidence: 99%